2015
DOI: 10.1002/pssa.201532613
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature annealing effects on the stability of Bi nanowires

Abstract: To investigate the physical properties of Bi nanowires and to explore their possible implementation in thermoelectric devices, it is essential to understand their chemical and thermal stability in air both at room and moderate temperatures. In this work, we study the influence of low temperature annealing processes on the morphology and composition of the wires by scanning and transmission electron microscopy and by Raman spectroscopy, revealing the formation of a metal oxide phase. This oxidation process init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In literature, TE organic p-type textile materials are already reported, using for example the conductive poly (3,4ehtylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS), and carbon nanotubes. [15,[32][33][34] On the other hand, reports of n-type organic textiles are rare due to the lack of air-stable ntype organic semiconductor materials. [35] Notable examples are the works of Ito et al, [36] demonstrating the fabrication of doped carbon nanotubes fibers with switchable p-and n-type behavior, and of Ryan et al, [21] reporting the fabrication of n-type yarns by coating commercial poly(ethylene terephthalate) (PET) with a composite of carbon nanotubes and poly(N-vinylpyrrolidone) (PVP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, TE organic p-type textile materials are already reported, using for example the conductive poly (3,4ehtylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS), and carbon nanotubes. [15,[32][33][34] On the other hand, reports of n-type organic textiles are rare due to the lack of air-stable ntype organic semiconductor materials. [35] Notable examples are the works of Ito et al, [36] demonstrating the fabrication of doped carbon nanotubes fibers with switchable p-and n-type behavior, and of Ryan et al, [21] reporting the fabrication of n-type yarns by coating commercial poly(ethylene terephthalate) (PET) with a composite of carbon nanotubes and poly(N-vinylpyrrolidone) (PVP).…”
Section: Introductionmentioning
confidence: 99%
“…silver) interconnections. [15,32,33,37,38] In this sense, the development of n-type textiles is the current challenge for a further boost of wearable TE generators.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoelectric (TE) devices are able to convert thermal energy into electrical power and vice versa, by exploiting the Seebeck and the Peltier effect, respectively. [1][2][3][4][5][6][7] Thus, depending on the device configuration, this technology can be used as TE generators (TEGs) or solidstate coolers (TECs), presenting several important advantages, such as pollutionfree energy conversion, low-maintenance needs (due to the absence of moving fluids or mechanical parts in the system), long operational lifetime, no working noise, and easy scalability in size and power. [8][9][10][11][12][13][14] Despite these positive features, the widespread usage of the TE technology is limited since the building blocks of current commercial devices are based on inorganic materials, [15][16][17][18][19] which are more efficient, but also heavier, rigid, more expensive, and mostly based on rare and/or toxic elements.…”
Section: Introductionmentioning
confidence: 99%
“…[55][56][57] Since the 1990s, studies on the n-doping process of semiconducting small molecule materials have been reported, investigating the correlation between the increase of the PF and both the doping conditions and the obtained material nano structure. [42,[58][59][60][61][62][63][64][65] Recently, an effective increase of the dopant miscibility was demonstrated through the replacement of the butric acid ester group with more polar oligo ethylene glycol side chains in solution processable n-doped [6,6]-phenyl-C 61 -butyric acid methyl ester, leading to superior values of both in-plane σ (7 S cm −1 ) and PF (≈47 µW m −1 K −2 ) [65] and also to an enhancement of the thermal stability of the doped materials. [42,64] Nonetheless, the ease of processability and printability from common organic solvents makes polymers more suitable for the fabrication of printed OTEGs.…”
Section: Introductionmentioning
confidence: 99%